2015
DOI: 10.1212/wnl.0000000000002079
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal kinesigenic dyskinesia

Abstract: PRRT2 mutations are common in patients with PKD and are significantly associated with an earlier age at onset, longer duration of attacks, a complicated form of PKD, combined phenotypes of dystonia and chorea, and a tendency for a family history of PKD. A patient with uniparental disomy resulting in a homozygous c.931C>T mutation is identified in the present study. Carbamazepine is the first-choice drug for patients with PKD, but an individualized treatment regimen should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…8 Neuroimaging of PKD-D, PKD-C or a mixture of both types has also failed to completely define specific neural characteristics that allow differentiation between these disorders. 9,10 At present, diagnosis of PKD mainly relies on these clinical characteristics, in the absence of reliable PKD-D- or PKD-C-specific neuromarkers.…”
Section: Introductionmentioning
confidence: 99%
“…8 Neuroimaging of PKD-D, PKD-C or a mixture of both types has also failed to completely define specific neural characteristics that allow differentiation between these disorders. 9,10 At present, diagnosis of PKD mainly relies on these clinical characteristics, in the absence of reliable PKD-D- or PKD-C-specific neuromarkers.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, point and frameshift mutations in PRRT2 were identified in 61.5%–100% of familial cases of PKD (Huang et al, 2015; Liu et al, 2013). Even in sporadic cases, the majority point and frameshift mutations of PRRT2 were inherited from unaffected parents (Ebrahimi‐Fakhari, Saffari, Westenberger, & Klein, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…PRRT2 is the most common causative gene for PKD. Mutations of PRRT2 , including point mutations and frameshift mutations, explain approximately less than one‐half of PKD cases (Huang et al, 2015), suggesting the presence of additional molecular pathogenic mechanisms. In this study, PRRT2 CNVs were identified in two patients with PKD, indicating that copy number deletion of PRRT2 is also a potential pathogenic factor for the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…먼저 (Yuan et al, 2012;Bae et al, 2011;Gao et al, 2011;Pech et al, 2010;Kaempgen et al, 2009;In et al, 2006 (Ning et al, 2016;Pei et al, 2016;Huang et al, 2015;Ramadoss and Kim, 2014 (Choi, et al, 2012;Li, et al, 2011;Chen, et al, 2010). …”
Section: 리그닌 기반 탄소나노섬유 매트 (Lcnfm)의 제조mentioning
confidence: 99%